LECTIN PROSPECTING IN COLOMBIAN LABIATAE. A SYSTEMATIC-ECOLOGICAL APPROACH - II. - PÉREZ GERARDO; VEGA NOHORA; FERNÁNDEZ-ALONSO JOSÉ LUIS (Caldasia)
This is the second study of lectin and mucilage detection in Labiatae nutlets from Colombia. It was carried out on 31 taxa belonging to 7 genera in which no previous studies have been carried out in this field. A differential response was observed in the group of genera and species studied in terms of mucilage presence as well as lectin activity which consistently increased following extract treatment with Pectinex. Lectin activity was detected in 28 species, being important (greater than 60% activity) in at least 75% of them. Genera such as Hyptis, Scutellaria, Aegiphila and Lepechinia, whilst not presenting mucilage, did present lectin activity, having high activity in most cases. By contrast, Salvia (in all sections studied) presented mucilage and important lectin activity.